Keragaman Bakteri pada Perairan Sabang, Provinsi Aceh - Lis Indah Sutiknowati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2018)
Sabang seawater have high diversity and its geographical condition allow hot springs to form, therefore, current research on this seawaters become important. The purpose of this study was to discover the quality and diversity of the seawaters based on microbiological aspects specifically the finding of coliform, heterotrophic, halotolerant and sulfur bacteria from several samples from the water and sediment sampling. Analysis and isolation process of the bacteria were using coliform and aerobic count plate petrifilm and specific media. The results indicated that there were coliform bacteria, heterotrophic and halotolerant bacteria and several of hot spring sources under the sea surface with extremely high density of sulfur bacteria as geothermal microbe.